Politeness Strategies Used In Complaint By Indonesian EFL Learners In Muhammadiyah University Of Surakarta - Pratiwi, Endah Hana; , Agus Wijayanto, Ph.D; , Dra. Malikatul Laila, M.Hum (2013)
This research describes the use of politeness strategies in complaint in relation to relative power (P) and distance (D) by Indonesian EFL learners in Muhammadiyah University of Surakarta. This involved descriptive qualitative research in which the research participants were thirty Indonesian EFL learners at first semester at English department, Muhammadiyah University of Surakarta. The data were spoken utterances of complaint strategies elicited through oral DCT (Discourse Completion Tasks) scenarios. The subjects were taken using the technique of proporsional random sampling comprising fifteen female and fifteen male participants. The data of compliant strategies were analyzed based on Trosborg (1995), whilst that of politeness were analized based on Brown and Levinson (1987). The research findings showed that Indonesian EFL learners tended to express annoyance when they made complaints. As for politeness, they mostly used bald on record and positive politeness. Social distance (D), rather than relative power (P), tended to influence the strategies of complaint and politeness.